Social Media Use Intensity, Cognitive Emotion Regulation, and Bullying Behavior among Junior High School Students: A Multiple Regression Analysis - Rohman, Faizal; Hafid (AL-ADABIYAH: Jurnal Pendidikan Agama Islam, 2026)
This study aimed to examine the effects of social media use intensity and cognitive emotion regulation on bullying behavior among junior high school students. The increasing use of social media among adolescents has raised concerns regarding its psychological and behavioral impacts, particularly bullying behavior in educational settings. This study employed a quantitative non-experimental design using a multivariate approach with multiple linear regression analysis. The research was conducted at SMP Negeri 1 Jatiroto, East Java, Indonesia, involving 61 students selected through purposive sampling. Data were collected using questionnaires measuring social media use intensity, cognitive emotion regulation, and bullying behavior. The data were analyzed using SmartPLS version 4 through descriptive statistics, assumption testing, t-test, F-test, coefficient of determination, and multiple linear regression analysis. The findings revealed that social media use intensity had a positive and statistically significant effect on bullying behavior (p = 0.025 < 0.05). In contrast, cognitive emotion regulation did not significantly affect bullying behavior (p = 0.904 > 0.05). Simultaneously, both variables significantly influenced bullying behavior (p = 0.001 < 0.05), although the model explained only 7.7% of the variance. The novelty of this study lies in integrating digital behavior and emotional regulation perspectives in explaining bullying behavior among adolescents. This study contributes theoretically to educational psychology and practically provides insights for schools and policymakers in developing digital literacy, emotional awareness, and anti-bullying programs in the digital era.